Serum Inflammatory and Immune Mediators Are Elevated in Early Stage Diabetic Nephropathy - Perlman, Alan S; Chevalier, James M; Wilkinson, Patrick; Liu, Hao; Parker, Thomas; Levine, Daniel M; Sloan, Betty Jo; Gong, Anna; Sherman, Raymond; Farrell, Francis X (Annals of clinical and laboratory science, 2015)
Diabetes is the leading cause of end stage renal disease (ESRD) in the United States, representing 44% of incident cases [1]. In this study, serum and peripheral blood collected from diabetic patients in five stages of chronic kidney disease (CKD), as defined by glomerular filtration rate (GFR), were compared to healthy (non-CKD) subjects. Serum samples were analyzed for 39 inflammatory or immune mediator protein levels and peripheral blood samples were analyzed for expression of 35 gene transcripts. In serum, MCP-1, FGF-2, VEGF, and EGF levels were elevated above controls at all stages of DN. Five mediator levels, GM-CSF, IL-1α, IL-1RA, IL-6, and MIP1β increased with disease progression until stage 4-5, at which point a decrease was observed paralleling a loss of functional renal mass that occurs in late stage CKD. Five mediator levels: GRO, IFNγ, MDC, Eotaxin, and G-CSF significantly differed from controls at one or more stages without apparent correlation with disease stage. Only a single mediator, sIL2RA, exhibited a linear increase with disease severity consistent with declining GFR. In peripheral blood, the transcript level of seven mediators, ICAM1, TNF-α, TGF-β, IL-8, IL17RA, IFNγ, and MYD88 were significantly elevated at all disease stages as compared to control. Statistically significant differences in protein and transcripts levels between diseased and control can be detected in serum and peripheral blood utilizing high content profiling. These changes occur as early as stage 1-2 before a significant decline in renal function.